Impact of the COVID-19 pandemic on the performance of pediatricians and pediatric dentists in the Brazilian Unified Health System - Davi Moreira Santana; Ricardo Barbosa-Lima; Alexandre Machado de Andrade (Revista Ciências em Saúde, 2023)
Objective: To evaluate the impact of the COVID-19 pandemic on the outpatient production of pediatricians and pediatric dentists in the Brazilian Unified Health System (SUS). Methods: An ecological study was carried out with an analytical and quantitative approach, using public domain data from the Department of Informatics of the SUS. The monthly number of professionals who worked in the SUS, the number of outpatient procedures in each category and the projection of residents from zero to thirteen years old to normalize it were retrieved. Data were compared by pre-pandemic (2018-2020) and pandemic (2020-2022) periods with a significance level of 5%. Results: There was a significant reduction in the monthly number of outpatient procedures performed in the SUS by pediatricians in the first and second pandemic year of COVID-19 when compared to the pre-pandemic period (p <0.001 e 0.002, respectively). This reduction represents a median percentage reduction of -57.1% (CI95% -51.3%, -71.7%) in the first and -22.3% (CI95% -0.55%, -31.5%) in the second pandemic year. Regarding pediatric dentists, a significant reduction was observed only between the pre-pandemic period and the first pandemic year (p <0.001), representing -82.0% (CI95% -73.4%, -93.6%). Moreover, a significant, positive and moderate correlation was observed between the productivity of both professional categories in the SUS throughout the investigated period (p < 0.001, ρ = 0.744). Conclusion: The COVID-19 pandemic negatively affected the provision of specialized medical and dental outpatient care for children in the SUS.